2023
DOI: 10.3390/app13106200
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freezing Raw Material on the Quality Changes and Safety of Salted Anchovies (Engraulis encrasicolus, Linnaeus, 1758) at Cold Storage Conditions

Abstract: This study demonstrates the effects of the freezing and frozen storage of anchovies prior to brining and dry-salting on quality changes and food safety during refrigerated storage (4 ± 1 °C). Fresh anchovies were divided into two groups, one of which was used as a control representing fresh raw material; the other was the experimental group and consisted of frozen and thawed anchovies stored at −18 °C for a year. Five different salt concentrations were used for brining (10, 15, 20, 25 and 30%) in addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Dama et al [ 22 ] showed that the protein content of Pseudotolithus typus decreased significantly (P < 0.05) after 21 days of freezing at −20 °C. During freezing, the formation of macrocrystals perforates cell membranes, promoting protein exudation and denaturation [ 47 ]. In the fresh fish, lipid content is higher significantly (P < 0.05) in E. fimbriata than in other species.…”
Section: Resultsmentioning
confidence: 99%
“…Dama et al [ 22 ] showed that the protein content of Pseudotolithus typus decreased significantly (P < 0.05) after 21 days of freezing at −20 °C. During freezing, the formation of macrocrystals perforates cell membranes, promoting protein exudation and denaturation [ 47 ]. In the fresh fish, lipid content is higher significantly (P < 0.05) in E. fimbriata than in other species.…”
Section: Resultsmentioning
confidence: 99%